Preparation Of Chemically modified sago waste for oil sorption - Muhamad Farid, Bin Mohammed Noh (Universiti Malaysia Sarawak, UNIMAS, 2012)
Oil spills are major concern due to their environmental and economical impact. This study investigates the raw sago waste (SW) and modified sago waste (MSW) as oil sorbents to recovery oil spills. SW dumped into the river can cause pollution because it largely composed of lignin and cellulose. The sago waste was modified via esterification process using acylation grafting with stearic acid. The SW and MSW were packed into nonwoven polypropylene bag formed “tea-bag kit” and their sorption behaviors were studied. The polypropylene exhibited high affinity oil absorption over the water. It is found that the MSW was significantly more hydrophobic than SW. Sorption tests with used engine oil (UEO) were conducted in dry system, wet static system and wet dynamic system. In this study, the MSW is the most suitable for application where the oil is to be removed from an aqueous solution. For the absorption in the absence of water, SW was an excellent absorbent. The density and hydrophobicity tests were also used to evaluate the sustainability of SW and MSW for the intended application. Utilization of sago wastes reduce the pollution effect and provide an economic solution for oil spill management to our environment.